2020
DOI: 10.1021/acsanm.0c01053
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Controlled Au-Decorated ZnO Heterojunction Nanostructures for NO2 Detection

Abstract: A comparative analysis of NO2 gas-sensing performances of geometry-controlled Au-decorated ZnO heterojunction nanostructures (nanospheres, nanorods, ultralong nanorods, and nanofibers) has been demonstrated with an emphasis toward exploration of their mechanistic pathways using in situ electrical and Raman spectroscopic studies. Room-temperature photo luminescence (RT-PL) studies indicate that the electron transfer from ZnO nanorods to Au nanocluster develops high resonant electron density with higher energy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
(134 reference statements)
1
22
0
Order By: Relevance
“…The results above showed that the decoration of the pristine ZnO structures with Au improves the gas sensing performance of the first, similarly to the previous literature results for noble metal modified ZnO systems [ 24 , 49 ]. The chemical composition of the Au@ZnO films corroborated the incorporation of gold (Au 0 , Au + , Au 3+ ) at the ZnO surface with a major presence of Au 0 (2.6 at.%) than Au + (1.8 at.%) or Au 3+ (0.7 at.%), suggesting the sensing mechanism of Au@ZnO films rely mainly on the metallic Au state.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results above showed that the decoration of the pristine ZnO structures with Au improves the gas sensing performance of the first, similarly to the previous literature results for noble metal modified ZnO systems [ 24 , 49 ]. The chemical composition of the Au@ZnO films corroborated the incorporation of gold (Au 0 , Au + , Au 3+ ) at the ZnO surface with a major presence of Au 0 (2.6 at.%) than Au + (1.8 at.%) or Au 3+ (0.7 at.%), suggesting the sensing mechanism of Au@ZnO films rely mainly on the metallic Au state.…”
Section: Resultssupporting
confidence: 89%
“…Recently, for instance, AACVD was employed to modify ZnO with iron and copper [ 3 ], although the gas sensing performance of these systems was not evaluated. Similarly, impregnation procedures based on the reduction of a chemical inorganic precursor were used to incorporate Ag and Au particles over ZnO [ 23 , 24 ]. However, these procedures usually do not include gold and silver preformed nanoparticles, as in the present work, and they were not employed for modifying gas-sensitive ZnO structures.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, this is the rst report of SWNTs' optical properties, working with any other transducer material layer that has been used as a means to detect and monitor N 2 O gas levels by an optical method; monitoring changes in effective refractive index and not an investigative spectroscopic analysis technique such as used in ref. 26. Importantly, such sensors have excellent regeneration and work at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…23. Additionally, Raman spectroscopic analysis produces spectra depending on the concentration of N 2 O at room temperature, 26 but this is a completely laboratory research method that is not available for remote sensing. Table 1 Summary of selected sensing performance of various schemes employed to detect nitrous oxide gases Comparing this detection approach to the conventional spectroscopy techniques described in the introduction, these have good limits of detection, but are laboratory based and are not suitable for remote sensing applications.…”
Section: Lodmentioning
confidence: 99%
“…Au electroless deposition (ELD) [16] represents an attractive solution-based method for decorating nanostructures, allowing low cost and versatility for depositing films or nanoparticles [17][18][19][20][21][22][23][24]. A reliable method for Au cluster decoration could be used in several applications such as DNA sensing [25], UV sensing [26], and gas sensing [27].…”
Section: Introductionmentioning
confidence: 99%